Environmental Education Infographics by Instagram: Digital Learning Material Increasing Motivation During the Covid-19 Pandemic - Habibah Rahmawati; Rizhal H. Ristanto; Mieke Miarsyah (International Journal on Advanced Science, Education, and Religion, 2021)
Learning activities during the Covid -19 pandemic were dominated by online learning, so digital learning materials are needed to help increase student learning motivation. The purpose of this development research is to develop digital learning material based infographic by instagram on environmental education that can increase student learning motivation in online learning during the Covid-19 pandemic. This development research uses a method that integrates the Borg and Gall models. The data obtained were through documentation, interviews, expert validation and provision of ARCS questionnaires. The results of the validity test based on the analysis of the expert's assessment data stated that this learning material fell into the "very valid" category with an average score of 3.66. During the learning process using infographic learning materials assisted by Instagram, there was an increase in student motivation with an initial percentage value of 54.25% to 83.75% after using the learning materials developed, the magnitude of the increase was obtained from the n gain test with a score of 0.67 in the moderate category. Keywords: Digital Learning Material, Environmental Education, Infographic b Instagram, Covid-19